Development and evaluation of inulin-loaded ethyl cellulose nanoparticles as oral prebiotic Supplement for selective eubiosis - LAKSHMINARAYANA T.S.,; BASAVARAJ MADHUSUDHAN, (International Journal of Pharma and Bio Sciences, 2017)
In recent days, ethyl cellulose polymer is being used in various biomedical applications due to its unique biocompatibility, non-toxicity and cost effectiveness. The aim of the present investigation was to prepare, characterize and evaluate the inulin-loaded ethyl cellulose nanoparticles. Inulin, a prebiotic, was encapsulated by the two-step desolvation process using ethyl cellulose. Characterization of the nanoparticles was performed using scanning electron microscopy (SEM), dynamic light scattering (DLS) and fourier transform infrared spectroscopy (FTIR). The nanoformulations were uniform in size, smooth surface, globular in shape and homogenous in nature. The mean average diameter of the nanoparticles was ranged between 174.2 and 217.9 nm and zeta potential was found to be -16.0±1.48 mV. From FTIR, it was clear that there was physisorption between the drug inulin and ethyl cellulose polymer. The drug loading capacity and entrapment efficiency of nanoparticles were found at 2.6% and 40%. The in vitro drug release profile exhibited a biphasic phenomenon indicating controlled drug release. The nanoformulations were found to be safe as evidenced by hemolysis assay. Based on the data available inulin-loaded ethyl cellulose nanoformulation would be a promising carrier system for the production of synbiotic system for oral delivery of probiotics.